Investigasi Kinerja Resistansi Pentahanan (Grounding) pada Lahan Rawa Timbun - Dian Eka Putra; Raden Ahmad Yani (SPEJ (Science and Physic Education Journal), 2021)
Abstract: This study aimed to determine the grounding resistance (grounding) in swampland. The method used in this research is to use the driven rod method. The investigation results through measurements with the 3 point method as well as with variations in depth and comparison of grounding resistance using a grounding rod made of coated copper with a resistance of 14.5 while the iron grounding rod is 16.70 or 15% larger than the copper grounding rod. In conclusion, In the investigation of the measurement of grounding resistance in swampland, copper-coated rod electrodes are more efficient than iron rods. Iron with rainy weather conditions. Keywords: Swamp Landfill, Measurement, Grounding Resistance